2017
DOI: 10.1097/mib.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-to-adult Transition and Medication Adherence in Patients with Inflammatory Bowel Disease

Abstract: TR patients did not have worse adherence than YAs diagnosed in adulthood. Protective factors may include previous treatment in pediatric centers and the salient symptomatology of inflammatory bowel disease, whereas increasing concerns over medications contribute to nonadherence in YAs. Pharmacist-led counselling improves adherence in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Indeed, it has recently been reported that pharmacists can have a major role in monitoring treatment plans and adverse events in biological treatment of rheumatological, gastroenterological, and dermatological pathologies [38]. Indeed, in patients with inflammatory bowel diseases, nonadherence to medication can be improved through pharmacist counseling [39,40]. Lastly, having a pharmacist involved in the clinical management of biological agents is believed to enhance the overall team model of patient care [41].…”
Section: Role Of the Pharmacistmentioning
confidence: 99%
“…Indeed, it has recently been reported that pharmacists can have a major role in monitoring treatment plans and adverse events in biological treatment of rheumatological, gastroenterological, and dermatological pathologies [38]. Indeed, in patients with inflammatory bowel diseases, nonadherence to medication can be improved through pharmacist counseling [39,40]. Lastly, having a pharmacist involved in the clinical management of biological agents is believed to enhance the overall team model of patient care [41].…”
Section: Role Of the Pharmacistmentioning
confidence: 99%
“…[53](Figure 2) The pronounced symptomology of diarrhoea and abdominal pain may favour medical adherence in adolescents with IBD, as opposed to other asymptomatic conditions. [54] It may be a challenge to achieve a "treat to target" approach by objective non-invasive monitoring using biomarkers such as FC, although that approach may be partially accepted in patients with mild symptoms.…”
Section: Perspectives and Barriers To Transition Carementioning
confidence: 99%
“…Jeganathan et al [54], in a cross-sectional cohort study, investigated adherence to medication using the In a relatively small study from Germany, structured transition of adolescents into adult health care led to relevant clinical and economic benefits. An important observation of this study was that delayed puberty was only noted in the group that transferred without structured transition.…”
Section: Why Do We Need a Transition Programme? Advantages Of Transitionmentioning
confidence: 99%
“…If done poorly, transition can affect not only the use of health services but also the patient’s health [89]. Although there have been few studies on patients with IBD, implementing an effective transition care program can help improve patients’ medication adherence and their health and life outcomes while promoting self-reliance [89,90].…”
Section: Outcomes Of Transitionmentioning
confidence: 99%